miR-1290 is a potential prognostic biomarker in non-small cell lung cancer - Mo, Dongping (J Thorac Dis, 2015)
BACKGROUND: miR-1290 is a newly discovered microRNA (miRNA), and its role in non-small cell lung cancer (NSCLC) remains unknown. This study aimed to evaluate the expression levels of miR-1290 in NSCLC tissues and serum, and explore its associations with clinicopathological characteristics and prognosis of NSCLC patients. METHODS: A total of 33 pairs of tissues and 73 serum samples were obtained from NSCLC patients and expression levels of miR-1290 were detected by specific TaqMan qRT-PCR. The relationship between miR-1290 expression levels in NSCLC tissues and serum and clinicopathological characteristics was estimated respectively. The correlation between serum miR-1290 expression levels and overall survival of NSCLC patients was performed by Kaplan-Meier analysis and Cox proportional hazards model. RESULTS: We determined that miR-1290 expression levels were increased significantly in NSCLC tissues compared with non-tumor adjacent normal tissues, and higher miR-1290 expression levels were positively correlated with high tumor stage (P=0.004) and positive lymph node metastasis (P=0.013). Compared with benign lung disease and healthy controls, serum levels of NSCLC patients exhibited higher expression of miR-1290. Furthermore, the up-regulation of serum miR-1290 more frequently occurred in NSCLC patients with high TNM stage, positive lymph node metastasis (P=0.022 and P=0.024, respectively). Kaplan-Meier analysis demonstrated that high serum miR-1290 expression levels predicted poor survival (P=0.022). Cox proportional hazards risk analysis indicated that miR-1290 was an independent prognostic factor for NSCLC. CONCLUSIONS: Our study suggests that miR-1290 is overexpressed in NSCLC, and serum miR-1290 may be used as a potential prognostic biomarker for NSCLC.